THE QUICK START: COFFEE BAR FOR STUDENTS AND TEACHERS OF TEI SFU - Aleksandra Nikolaevna Ivanova; Marina Sergeevna Volhonskaya; Elena Vladimirovna Goraschenko (Современная наука и инновации)
Currently, in Russia and, in particular, in Krasnoyarsk, there is an active development of the coffee house market. Recently, in Krasnoyarsk, there has been strong competition between coffee houses. Therefore, many coffee shops use different ways to attract visitors.